BUSINESS RISK MANAGEMENT AND ENVIRONMENTAL COMPLIANCE: A REVIEW OF SHELL OIL SPILLS IN SYDNEY HARBOUR AUSTRALIA - Larasati, Ika Putri (Jurnal Ekonomi Modernisasi, 2011)
A business risk has been an inherent part of companies’ activities nowadays. It relates to threats and opportunities which make a majority of companies manage the risk. The business risk also has been concerned by public particularly in term of environmental risk. A failure to manage the environment may result in negative reactions from public. The negative reactions are predicaments for company’s economy. Therefore, companies have also considered the significance of the environmental risk management. An example of these companies is Shell Oil Company which suffered environmental issue in 1999. Accordingly, this paper aims to evaluate the risk management conducted by the Shell Company which focuses on company’s effort to maintain good relationship with stakeholders in its environmental risk management. There were determinant factors in the successful risk management. The first factor is an efficient and effective implementation of risk management cycle. Secondly, a practice of risk management phase. The third factor is effective social activities. The fourth factor is a significance of risk management application since the establishment of company. The fifth factor is an importance of efficient and effective communication with stakeholders. Finally, a substantial contribution from media is prominent aspect in company’s risk management.